Elastomers Grow into Actuators. Issue 12 (13th February 2023) - Liang, Huan; Wu, Yahe; Zhang, Yubai; Chen, Erqiang; Wei, Yen; Ji, Yan
Abstract: It is common knowledge that when an elastomer (rubber) is stretched, its length will be maintained if its two ends are fixed. Here, it is serendipitously found that when an elastomer is slowly elongated further to achieve buckling under such conditions, the final length is much longer than the pre‐stretched length. This allows the design of untethered autonomous synthetic‐material‐based soft robots that do not need any other chemical or electrical energy sources or external stimuli after the pre‐strain is installed. Once the growth starts, the elongation continues to proceed even when the applied force is removed. Moreover, the elastomer, after growing, eventually forms a robust soft actuator that can be reshaped for different purposes. Few synthetic materials can grow like this, so far. This investigation shows that the material has an uncommon liquid crystal phase. Contrary to normal liquid crystals, it becomes birefringent only at high temperatures. The formation and the reshaping of the resulting soft actuators relate to a usually unnoticed reversible reaction. The work is promising to promote further understanding of dynamic covalent chemistry and liquid crystal elastomers, as well as to foster new designs and high‐impact applications of bioinspired sustainable soft actuators in areas other than soft robots. Abstract : An elastomer that can grow automatically and finally becomes a soft actuator is presented. The whole process does not need energy input or external stimuli other than a single pre‐stretch. The growth can output mechanical work. The material has an uncommon liquid crystal phase. The formation of soft actuators is associated with a usually unnoticed reaction.